Social media content analysis: Study on brand posts of electronics companies - Rahman, Zoha; Suberamanian, Kumaran; Zanuddin, Hasmah; Md Nasir, Mohd Hairul Nizam (2016)
Social Media is considered as a first-rate open communication platform to connect directly with customers. One of the most noteworthy customs to connect with the consumers through these Social Networking Sites (SNS) is to create a Facebook fanpage with brand contents and to place different posts periodically on these fanpages. According to different posts or contents placed on the fanpages, consumer responses in different manners. Usually users click like button on particular brand fanpages and then put like, comments or keep sharing on particular posts of fanpages. These types of consumer activities in fanpages reflect brands' post interactivity and engagement. Most importantly, in measuring social networking sites' effectiveness, corporate houses are now analyzing metrics in terms of calculating engagement rate, number of comments/share and likings in fanpages .So now, it is very vital for the e- marketers to identify the effectiveness of different contents or posts of fanpages in order to increase the fan engagement rate in the fan pages. In the study the authors have used the Netnographics technique and analyzed total 1325 brand posts from 17 international brands of Electronics companies. Data of 8 months (From September 2015- April 2016) have been collected for analyses, which were available online from Brand' fan pages. Finally the authors analyzed the descriptive statistics (Post frequency, post engagement metrics) of different posts in each Brand fanpages. The study elaborated the types of post in fan pages and their implication on generating users' engagement activities. Findings discovered two types of post (Image with detai Is and feature video post) most effective in producing user engagement. The descriptive statistics will guide the e-marketers of Electronics companies to have a comprehensive idea on social media content strategy.